2020
DOI: 10.21776/ub.afssaae.2020.003.02.6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding rice straw charcoal to the processing of bio-pellet from cacao pod husk

Abstract: Cacao pod husk and rice straw charcoal are potentially transformed into bio-pellet because of their high calorific value. Cocoa pod husk and rice straw charcoal has a calorific value of 4974.837 cal/g and 3569.837 cal/g, respectively. This research aimed to identify the effect of variations in particle size and in the addition ratio of rice straw charcoal on the calorific value of bio-pellet. Randomized block design factorial were employed in this study with factor of the addition ratio of rice straw charcoal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…raw residual of coconut milk, pineapple juice, and tuna juice) [14]; biodiesel from sugar beet agro-industrial waste [15]; biohydrogen from molasses, vinasse and bagasse [16]; and bio-pellet production from cacao agro-industrial waste (i.e. cacao pod husk) [17]. .…”
Section: Introductionmentioning
confidence: 99%
“…raw residual of coconut milk, pineapple juice, and tuna juice) [14]; biodiesel from sugar beet agro-industrial waste [15]; biohydrogen from molasses, vinasse and bagasse [16]; and bio-pellet production from cacao agro-industrial waste (i.e. cacao pod husk) [17]. .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported making briquettes using biomass other than rice husks [8], such as using cocoa pods [9][10], peanut shells [11], cotton stalks [12], corn cobs [13][14][15][16], and coconut shells [11; 17]. However, rice husk utilization as briquetting material is always attracting due to its huge generation following food production, mainly in Asia and Africa [18].…”
Section: Introductionmentioning
confidence: 99%